Strategi Komunikasi Humas Dinas Kesehatan Kota Bandung dalam Penyelenggaraan Vaksinasi Covid-19 Pada Masyarakat Kota Bandung - Wardoyo, Hartantio Kusumo; Muhtadi, Asep Saeful; Fatoni, Uwes (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the communication strategy process in the covid-19 vaccination activities of the Public Relations of the Bandung City Health Office. This research was conducted using descriptive qualitative methods using primary data sources and secondary data, and the data collection techniques used were through observation, in-depth interviews, and documentation. The results of the research obtained by the Public Relations of the Bandung City Health Office have implemented a communication strategy, namely by means of; 1) Defining Problems: situation analysis, media analysis and target target analysis; 2) planning and Programming: setting goals and formulating plans; 3) taking action and communicating: coordination and dissemination of information; 4) evaluation: monitoring and response, and listening to community criticism & suggestions.